The Analysis of Factors Influencing Exclusive Breastfeeding Given By Working Mothers - Yayuk Fatmawati; Biyanti Dwi Winarsih; Hirza Ainin Nur (South East Asia Nursing Research, 2020)
Breast milk is a food source for infants with essential nutrition for their health, growth, and development. Breast milk has various benefits including preventing children from a variety of conditions that can inhibit their growth and development such as malnutrition. Malnutrition is associated with 45% of deaths and illnesses of children. Exclusive breastfeeding is considered to be able to help overcome nutritional problems such as stunting and malnutrition. A report from the Ministry of Health Republic of Indonesia in 2015 showed that 18.8% of toddlers suffer from malnutrition while 12.7% experience stunting. This study aimed to analyse factors influence breastfeeding given by working mothers. This was a quantitative descriptive study with a cross-sectional approach. The study involved 101 respondents who were working mothers of children aged 7-24 months old. The respondents were selected using questionnaire measurement tools. Data analysis used the Chi-Square test with an alpha value of 0.05. The results show that there was no relationship between knowledge of breastfeeding and exclusive breastfeeding. However, there was a significant relationship between family support and exclusive breastfeeding. Good knowledge must be followed by a good attitude and family support, especially from the husband, so that the mother will give exclusive breastfeeding to the baby.